Magnetohydrodynamics forced convection of nanofluid in multi-layered U-shaped vented cavity with a porous region considering wall corrugation effects - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
Magnetohydrodynamics forced convection of CNT-water nanofluid in a layered U-shaped vented cavity involving a porous region is investigated under the impact of wall corrugation. The numerical study is performed by using the finite volume method. Impacts of Reynolds number (between 100 and 1000), Hartmann number (between 0 and 50), Darcy number (between 10(-4) and 5 x 10(-2)), porous layer height (between 0.1H and 0.5H), height (between 0 and 0.5H) and number of triangular waves (between 1 and 16) and curvature (between 0.01H and 0.2H) at the U-turn of the vented cavity on the convective heat transfer features are examined. The flow field and heat transfer are affected by variations in the Reynolds number, magnetic field strength and permeability of the porous medium. The average Nusselt number increases significantly with higher magnetic field strength and at Hartmann number of 50, the amount of enhancement is 112% while the impact is reverse for highest value of Darcy number of the porous compound. The corrugation of the bottom wall which is a triangular wave was found to be used as an effective tool for fluid flow and heat transfer features. The average heat transfer rate reduces with higher number of corrugation waves (68.2% reduction) while it first increases then reduces with higher height of the corrugation. The curvature of the neck in the U-shaped cavity reduced the heat transfer rate which is 15.5% at the highest value.
Keywords: Porous layer; U-shaped vented cavity; Corrugation; Convection; Finite volume method; Nanofluid